Answer:
1) ![y=-\frac{1}{4}x+\frac{1}{2}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B4%7Dx%2B%5Cfrac%7B1%7D%7B2%7D)
2) ![y=4x+5](https://tex.z-dn.net/?f=y%3D4x%2B5)
3) ![y=-\frac{1}{4}x+4](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B4%7Dx%2B4)
Step-by-step explanation:
<em><u>Question 1:</u></em>
All you have to do is solve for y to get the slope intercept form.
![4x+16y=8\\16y=-4x+8\\y=-\frac{1}{4}x+\frac{1}{2}](https://tex.z-dn.net/?f=4x%2B16y%3D8%5C%5C16y%3D-4x%2B8%5C%5Cy%3D-%5Cfrac%7B1%7D%7B4%7Dx%2B%5Cfrac%7B1%7D%7B2%7D)
So the equation is ![y=-\frac{1}{4}x+\frac{1}{2}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B4%7Dx%2B%5Cfrac%7B1%7D%7B2%7D)
<em><u>Question 2:</u></em>
Now for this one you have to find the line perpendicular to the previous equation.
<em> Finding the slope:</em>
So first we need to find the slope and usually the slope of a perpendicular line is the opposite and the reciprocal to the original equation. So instead of
it will be
or even easier to manage
.
<em> Finding the y-intercept:</em>
For the y-intercept we need to plug in what we know into this formula....![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
We know the slope is
and we could use the ordered pair that they provided us with
. The -6 is the x and the -19 will be the y. Now let's plug in and solve.
![y=mx+b\\-19=4(-6)+b\\-19=-24+b\\b=5](https://tex.z-dn.net/?f=y%3Dmx%2Bb%5C%5C-19%3D4%28-6%29%2Bb%5C%5C-19%3D-24%2Bb%5C%5Cb%3D5)
<em> Writing the equation:</em>
Now we know all the information needed to write the equation.
![y=mx+b\\m=4\\b=5](https://tex.z-dn.net/?f=y%3Dmx%2Bb%5C%5Cm%3D4%5C%5Cb%3D5)
Now we just fill it in the formula...
![y=4x+5](https://tex.z-dn.net/?f=y%3D4x%2B5)
<em><u>Question 3:</u></em>
For a parallel equation the slope will be the same in order for them to be parallel to each other.
<em> Finding the y-intercept:</em>
For the y-intercept we need to plug in what we know into this formula....![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
We know the slope is
and we could use the ordered pair that they provided us with
. The -8 is the x and the 6 will be the y. Now let's plug in and solve.
![y=mx+b\\6=-\frac{1}{4}(-8)+b\\6=2+b\\b=4](https://tex.z-dn.net/?f=y%3Dmx%2Bb%5C%5C6%3D-%5Cfrac%7B1%7D%7B4%7D%28-8%29%2Bb%5C%5C6%3D2%2Bb%5C%5Cb%3D4)
<em> Writing the equation:</em>
Now we know all the information needed to write the equation.
![m=-\frac{1}{4}\\b=4](https://tex.z-dn.net/?f=m%3D-%5Cfrac%7B1%7D%7B4%7D%5C%5Cb%3D4)
Now we just fill it in the formula...
![y=-\frac{1}{4}x+4](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B4%7Dx%2B4)